The Village Movement Against Money Politics (APU): Bawaslu's Preventive Strategy in Preventing Money Politics - Nur Kholis; Sayyida Faradiba Vahlevi; Octavia Novita Sari; Muhammad Irfan; Maria Elida Tarigan (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2026)
Abstract: Regional elections serve as a channel for public aspirations in choosing local leaders, yet they remain vulnerable to money politics. This study examines the factors behind money politics, Bawaslu’s preventive strategies through the Village Movement Against Money Politics (APU), and regional elections from Jurgen Habermas’s public sphere perspective using a literature study method. The findings show that money politics is driven by economic resource crises, value crises, weak legal legitimacy, and limited political understanding. Bawaslu addresses this issue through preemptive and preventive strategies, including anti-money politics declarations, workshops, citizen dialogue literacy, complaint posts, collaboration with election monitoring communities, voter socialization, and anti-money politics patrols. Public spaces, both physical and digital, are utilized to strengthen political education and democratic integrity.